Konsep Pendidikan Akhlak dalam Kitab Akhlak Lil Banin Karya Syekh Umar Bin Ahmad Baraja - M Hasyim Abdurrohman; Rifqi Aulia Rahman; Noor Aziz (Reflection : Islamic Education Journal, 2025)
Moral education is the core of Islamic teachings that emphasize the formation of noble character in human relationships with Allah SWT and with others. The phenomenon of moral deterioration that occurs in society, such as promiscuity, juvenile criminality, violence, and the loss of manners towards parents and teachers, shows the urgency of systematic moral education. This research aims to examine the content and content of the book Akhlak Lil Banin by Sheikh Umar bin Ahmad Baraja' and the strategy of the moral education concept contained in it. The research method used is a literature study with a qualitative-descriptive approach through content analysis. The results of the study show that Lil Banin's book of Morals contains fundamental moral values, including ethics with parents, manners with teachers, speaking ethics, honesty and trust, responsibility, and manners of eating and drinking. The moral education strategy in this book includes moral development towards Allah SWT, oneself, parents, teachers, fellow humans, the environment, and in all life circumstances. Thus, Lil Banin's book of Morals is not only a moral guideline for children and adolescents, but also relevant as a reference for character education in the modern era that is full of moral challenges.